A rare case of metastatic lung cancer to the bladder - Karle, William; Barazani, Yagil; Tareen, Basir (Canadian Urological Association Journal, 2013)
Cancer metastasis to the bladder from non-contiguous sites is very rare. Lung metastasis to the bladder is even more uncommon, with an extensive literature search identifying only four documented cases in the past 20 years. Of these four cases, only one was from lung adenocarcinoma. In this report, we present the case of a 66-year-old male with known lung adenocarcinoma found to have the incidental finding of a bladder mass upon computed tomography imaging. Histochemical staining of samples from the bladder confirmed metastatic dissemination from the primary lung malignancy.